A commentary on Diagnosing Cushing's disease in the context of renal failure. Issue 4 (October 2019) - Raff, Hershel; Cohen, Eric P; Findling, James W
Abstract : The diagnosis of endogenous hypercortisolism (Cushing's syndrome) is extremely challenging. Chronic kidney disease (CKD) increases the activity of the hypothalamic-pituitary-adrenal axis making the diagnosis of Cushing's syndrome even more challenging. This is particularly so since urine free cortisol (UFC) testing is not useful in CKD. The case report by Stroud et al . in this issue of the European Journal of Endocrinology highlights this problem by finding normal UFC in a patient with pituitary ACTH-dependent Cushing's syndrome. Elevated late-night salivary cortisol (LNSC) testing was diagnostic and pituitary adenomectomy was curative. LNSC measurement is the diagnostic test of choice in patients with suspected Cushing's syndrome, particularly in the presence of CKD..